2019
DOI: 10.1002/tox.22761
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin activates Hippo pathway and JNK/ERK/AP‐1 signaling to inhibit proliferation and induce apoptosis of human osteosarcoma cells via ZAK overexpression

Abstract: Osteosarcoma (OS) is a tumor entity that can cause a large number of cancer-related deaths. Although chemotherapy can decrease proliferation and increase apoptosis of human OS cells, the clinical prognosis remains poor. Fisetin is a flavonol found in fruits and vegetables and is reported to inhibit cell growth in numerous cancers. But the molecular mechanism underlying fisetin in human OS cells is not clear. It is known that sterile-alpha motif and leucine zipper containing kinase (ZAK), a kinase in the MAP3K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…[17][18][19] It was recently reported to have antiproliferative and apoptotic activity in various cancer cell lines, including human head and neck cancer, osteosarcoma, breast cancer, and renal cancer stem cell, suggesting that it could be used as a novel anti-cancer agent. [20][21][22][23] We previously confirmed that fisetin inhibited malignant proliferation in human OSCC by blocking the Met/Src signaling pathway. 24 However, no crucial downstream molecular targets for the anti-proliferation effect of fisetin in OSCC have yet been identified.…”
Section: Introductionmentioning
confidence: 69%
“…[17][18][19] It was recently reported to have antiproliferative and apoptotic activity in various cancer cell lines, including human head and neck cancer, osteosarcoma, breast cancer, and renal cancer stem cell, suggesting that it could be used as a novel anti-cancer agent. [20][21][22][23] We previously confirmed that fisetin inhibited malignant proliferation in human OSCC by blocking the Met/Src signaling pathway. 24 However, no crucial downstream molecular targets for the anti-proliferation effect of fisetin in OSCC have yet been identified.…”
Section: Introductionmentioning
confidence: 69%
“…Fisetin and other flavonoids have been shown to regulate cell functions, i.e., regulation of vascular smooth muscle contractility [7], protecting against hepatic steatosis [8], also has beneficial effects on anti-neurodegenerative and neuroprotective function [3]. Mechanistically, fisetin could regulate cell function by affecting several important signaling pathways, including PI3K/Akt [9,10], JAK/STAT [11,12], AMPK [8,13], and the Hippo signaling pathway [14]. Furthermore, fisetin can regulate the levels of various growth factors and proinflammatory cytokines, i.e., prostaglandin E2, tumor necrosis factor-alpha (TNF-alpha), interleukin (IL)-1beta, IL-6, and IL-8 depending on the flavonoid structure and the cell types involved [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that fisetin treatment can alter activity of Hippo signaling pathway as fisetin can upregulate expression of leucine zipper containing kinase (ZAK), a kinase in the MAP3K family, to induce the activity of Hippo pathway core-kinases, MST1/2 and LAT1/2, and mediate the activation of JNK/ERK. Activation of these kinases resulted in apoptosis of osteosarcoma cells [14]. We have recently shown that Yes-associated protein (YAP), a transcriptional coactivator that is negatively regulated by Hippo pathway core-kinases, plays a critical role in regulating adipo-osteogenic lineage differentiation of human MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…JUN is also called as transcription factor AP-1, which is a dimer composed of c-jun protein and c-fos protein family members. With the function of regulating the release of many inflammatory factors, such as IL-1 β, TNF-α, IL-6, IL-8, etc., activated AP-1 is called the third messenger of intracellular signaling, and it also plays a regulatory role in cell proliferation, differentiation, apoptosis and inflammation [24]. Lim et al [25] study found that the blocking of the signaling pathways p38 MAPK/AP-1 and JAK2/STAT1/2 can significantly reduce the release of MMP-13 in chondrocytes treated by IL-1β, thus exerting the effect of protecting cartilage degeneration [26].…”
Section: Discussionmentioning
confidence: 99%